2022
DOI: 10.1021/acs.jpclett.2c03040
|View full text |Cite
|
Sign up to set email alerts
|

Laser Spectroscopy of Aromatic Molecules with Optical Cycling Centers: Strontium(I) Phenoxides

Abstract: We report the production and spectroscopic characterization of strontium­(I) phenoxide (SrOC6H5 or SrOPh) and variants featuring electron-withdrawing groups designed to suppress vibrational excitation during spontaneous emission from the electronically excited state. Optical cycling closure of these species, which is the decoupling of the vibrational state changes from spontaneous optical decay, is found by dispersed laser-induced fluorescence spectroscopy to be high, in accordance with theoretical predictions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…To investigate the influence of metal atom on anharmonic vibrational coupling, we also studied two strontium phenoxides, SrOPh and SrOPh-3,4,5-F 3 . Previous study 17 has provided low-resolution DLIF spectra for these molecules. Figures 4a and 4b displays the higher resolution DLIF spectra recorded here for SrOPh from the excited A ̃and B ̃states.…”
Section: The Journal Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the influence of metal atom on anharmonic vibrational coupling, we also studied two strontium phenoxides, SrOPh and SrOPh-3,4,5-F 3 . Previous study 17 has provided low-resolution DLIF spectra for these molecules. Figures 4a and 4b displays the higher resolution DLIF spectra recorded here for SrOPh from the excited A ̃and B ̃states.…”
Section: The Journal Ofmentioning
confidence: 99%
“…Functionalizing large molecules with optical cycling centers (OCCs) is being explored as a means for extending the exquisite control available in quantum information science to the chemical domain. Success requires that these OCCs absorb and emit many photons without changing their vibrational states. To accomplish this task, molecular design rules are being developed, aided and validated by experiments, to guide the creation of the ideal quantum functional groups. For example, prior work has demonstrated that alkaline earth alkoxides provide a general and versatile chemical moiety for optical cycling applications, as the alkaline earth radical electron can be excited without perturbing the vibrational structure of the molecule. ,, Similarly, traditional physical organic principles, such as electron-withdrawing, have been shown to improve OCCs performance. , Further, experimental and theoretical extensions to more complex acenes, , diamondoids, and even surfaces suggest an exciting path forward for creating increasingly complex and functional quantum systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the identification of promising laser-coolable molecules using both high-resolution spectroscopy and quantum-chemical calculations plays a key role in the laser cooling of molecules. The experimental measurements of vibronic branching ratios using high-resolution laser spectroscopy , have recently been combined with optical cycling to further enhance the sensitivity of the measurement . Theoretical and computational tools are also being developed, aiming to provide useful information about optical cycling transitions.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that compound 2 can also be constructed as a derivative from the neutral Sr + -phenoxide complex, as extensively discussed in ref , through “cationization” of the neutral OCC-containing complex by adding the positively charged trimethyl­ammonium group N + (CH 3 ) 3 . Though both views are formally equivalent, it is worth noting that the lowest-energy dissociation channel of the complex corresponds to the dissociation into Sr + and the zwitterion.…”
mentioning
confidence: 99%